Sensitivity of expressive linguistic domains to surgery age and audibility of speech in preschoolers with cochlear implants. (2nd January 2018) - Nicholas, Johanna G.; Geers, Ann E.
Abstract : Objectives: To determine whether relative delays among domains exist in the conversational use of vocabulary, syntax, and morphology by children with cochlear implants (CIs) and whether these were differentially affected by age of implantation (AOI) and the audibility of speech. Methods: Participants in this short-term longitudinal study were 126 children with AOI of 6–38 months and a matched group of 30 children without hearing loss. Language samples of the same children at ages 3.5 and 4.5 were analyzed for the breadth of vocabulary and bound morphemes used, and sentence length. Results: At both test ages, expressive language domains were delayed equally. Higher performance across domains was independently associated with younger AOI and better pre-implant-aided thresholds. No domain was affected differently by very early implantation, but bound morpheme breadth was associated with better CI-aided thresholds. Between 63 and 78% of children with AOI of 6–11 months scored close to hearing age-mates by 4.5, a level achieved by fewer than 25% of those with AOI of 19–24 months or later ages. Discussion: Previous studies indicated greater language delays in the areas of morphology and syntax than those of vocabulary, with the earliest ages of implantation conferring the greatest benefit to those domains. The current design addressed inconsistency across studies in modes of communication used, presence/absence of other disabilities, and differences in language domains chosen as outcome measures. Conclusions: Linguistic domains benefitted equally from early implantation, regardless of the duration of auditory stimulation. Better pre-CI-aided hearing often compensated for later AOI. Bound morpheme use was greater with better CI-aided thresholds.